Beneficiation Process of Kyanite-Rich Mineral Assemblages from Thassos Island Aegean Sea, Greece. (3rd October 2022) - Gogou, Alexandra; Mavrogonatos, Constantinos; Anastasatou, Marianthi; Voudouris, Panagiotis; Chryssoulis, Stephen; Stamatakis, Michael
ABSTRACT: Kyanite-rich rock samples from Thassos Island, Greece, underwent beneficiation tests aiming to examine their potential as commercial refractory materials. The extracted material was compared to commercial samples of kyanite, andalusite and sillimanite. The experimental procedure combined mineral processing and material characterization. The mineral processing included grinding of the Thassos samples and grain size distribution, then gravity separation, using heavy liquid media (sodium polytungstate), and magnetic separation. Material characterization included XRF analysis on the bulk samples, XRD analysis on both the bulk and the commercial samples, and combined reflected light microscopy, SEM, XRF and XRD analysis on the final product. Gravity separation tests showed that the optimum liberation size of kyanite is any grain size finer than 500 μm, since coarser grain size fractions are characterized by elevated content of accessory minerals in the concentrates. Magnetic separation followed, removing the magnetic minerals from the concentrates, with ilmenite being a possible Ti-rich by-product to be recovered. The results indicate that the obtained percentage of kyanite reaches up to 95%. Furthermore, chemical analysis reveals that the composition of the processed material, in terms of concentration of alumina (and other major oxides), meets the standards of the Chinese and the American industry. It is therefore suggested that the Thassos kyanite-bearing assemblages constitute a promising resource that should be further tested in a semi-industrial scale, to fully establish their industrial potential.